Exploration of Wireless Multimedia Sensor Network Based on Joint Photographic Experts Group Image Coding Algorithm - He, Jie (International Journal of Online and Biomedical Engineering, 2019)
to study the performance of image coding and image transmission of wireless video sensor node in wireless multimedia sensor network, the challenges and design objectives of image coding technology in wireless multimedia sensor network are discussed, and the classification and exploration are carried out from two aspects: individual source coding and distributed source coding. The compression of video monitoring image sequence in wireless multimedia sensor network is studied and a low complexity image coding scheme based on change detection and improved Joint Photographic Experts Group (JPEG) algorithm is proposed. The moving target in the monitoring image is located with the change detection algorithm, that is, the area of interest. Only the region of interest is transmitted to reduce the quantity of data transmission and adapt to the limited storage and forwarding capability of wireless sensor nodes; The Discrete Cosine Transform (DCT) and quantization processes in Joint Photographic Experts Group (JPEG) algorithm are improved to reduce the computational complexity and adapt to the limited computing power of wireless sensor nodes.The analysis of algorithm complexity and the results of simulation experiment show that the proposed method can effectively reduce the data communication amount of wireless sensor nodes and the energy consumption in the calculation process while ensuring the image quality required by the application.Wireless multimedia sensor network is a new and interdisciplinary subject.The study of it is also multidirectional and multi-angle.The image coding algorithm of wireless multimedia sensor network is studied deeply.Although some achievements have been made, there are still a lot of problems that need to be further studied.